Digital literacy-based learning strategies in shaping media-wise characters in the modern young generation - Sarbaitinil Sarbaitinil; Rr. Dina Kusuma Wardhani; Nurita Putranti; Adam Latuconsina; Mesrawati Rifai (Indonesian Institute for Counseling, Education and Theraphy, 2026)
The development of digital technology has brought significant changes to the communication patterns, information access, and social interactions of the modern young generation. However, the high intensity of digital media use is also accompanied by various problems such as the spread of hoaxes, cyberbullying, hate speech, and low awareness of digital ethics. This study aims to analyze digital literacy-based learning strategies in shaping wise media character in the modern young generation. The study used library research methods with data collection techniques through documentation studies of various books, scientific journals, articles, and relevant research results. Data were analyzed using content analysis techniques to identify patterns, relationships, and key findings related to digital literacy and media character. The results show that digital literacy-based learning strategies, such as critical, collaborative, reflective, and project-based learning, can improve critical thinking skills, digital ethics awareness, social responsibility, and the ability to filter information appropriately. Thus, digital literacy plays a crucial role in supporting the character formation of a young generation that is intelligent, ethical, and wise in using digital media.